Hyperthermic intraperitoneal chemotherapy enhances survival outcomes in primary ovarian cancer following cytoreductive surgery: a systematic review and meta-analysis - Sun, Qian; Hu, Kangshuo; Chen, Jingqi; Chen, Yixia; Xie, Zhongxuan; Guan, Yuqing; Ying, Yuqing (Frontiers in Oncology, 2025)
BackgroundThis study aimed to evaluate the therapeutic effect of hyperthermic intraperitoneal chemotherapy (HIPEC) in patients with primary ovarian cancer (OC) following cytoreductive surgery (CRS).MethodsFollowing the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, we searched PubMed, Web of Science, Embase, and the Cochrane Library from inception to May 2025. The outcomes were progression-free survival (PFS) and overall survival (OS). Treatment effects were quantified using pooled hazard ratios (HRs) with 95% confidence intervals (95%CIs).ResultsThis meta-analysis included 10 studies [three randomized controlled trials (RCTs) and seven observational studies] involving 1,668 patients. Patients with primary OC undergoing CRS who received HIPEC treatment in the experimental group demonstrated prolonged PFS (HR = 0.45, 95%CI = 0.29–0.69, p < 0.001, I2 = 77.3%) and OS (HR = 0.59, 95%CI = 0.45–0.78, p < 0.001, I2 = 60.6%) outcomes compared with the controls. In the experimental group, better PFS benefits were observed in Western populations, observational studies, interval cytoreductive surgery (ICS), and in patients with Eastern Cooperative Oncology Group (ECOG) 0–1. HIPEC was beneficial for patients with OC regardless of follow-up time ≥5 years (HR = 0.68, 95%CI = 0.49–0.96, p = 0.026) or <5 years (HR = 0.29, 95%CI = 0.13–0.63, p = 0.002), with a greater magnitude of benefit observed in the subgroup with follow-up <5 years. The subgroup analyses for OS revealed a consistent benefit of HIPEC across Western population, follow-up time ≥5 years, ICS, and ECOG 0–1. Benefit was associated with HIPEC in both RCT (HR = 0.75, 95%CI = 0.60–0.94, p = 0.013) and observational analyses (HR = 0.47, 95%CI = 0.33–0.68, p = 0.001), while the observed effect size was larger in the latter. Conversely, HIPEC was associated with a significant OS detriment in patients with an ECOG performance status of 2–3 (HR = 2.37, 95%CI = 1.07–5.23, p = 0.033).ConclusionHIPEC appears beneficial to the prognosis of patients with primary OC following CRS, particularly after ICS. However, the administration of HIPEC in patients with ECOG 2–3 requires careful clinical consideration.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251036731.